ANALISIS KELAYAKAN FINANSIAL AGROINDUSTRI KERIPIK NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Yona Purba; Jum'atri Yusri; Roza Yulida (Indonesian Journal of Agricultural Economics, 2017)
This research aimed to analyze the financial feasibility of pineapple chips agroindustry in Kualu Nenas Village. Investment criteria used in analyzing the financial feasibility were Net Present Value (NPV), Internal Rate of Return (IRR) and Net Benefit Cost Ratio (Net B/C). The results of the research showed that pineapple chips agroindustry is feasible to run with production of 9 kg with the NPV value of IDR 257.628.276, Net B/C of 3,52 (Net B/C is more than 1) and IRR of 64,42%. If the production is 6 kg in one day, pineapple chips agroindustry is feasible to run with the NPV value of IDR 96.910.084, Net B/C of 1,84 (Net B/C is more than 1) and IRR of 31,68%. The sensitivity analysis showed that if there is a 20% increase in pineapple raw material prices, an increase in the price of cooking oil of 4%, and fixed output price during the life of the business, then the pineapple chips agroindustry business is still feasible with either 9 kg or 6 kg production per day. If there is a decrease in the scale of production on a 9 kg production scale, this business is still feasible to run. This business is no longer feasible if there is a decrease in production on a production scale of 6 kg per day.